A Two-steps Fixed-point Method for the Simplicial Cone Constrained Convex Quadratic Optimization - KHALDI, Merzaka; ACHACHE, Mohamed (Studia Universitatis Babeș-Bolyai Mathematica, 2024)
In this paper, we deal with the resolution of the simplicial cone constrained convex quadratic optimization (abbreviated SCQO). It is known that the optimality conditions of SCQO is only a standard linear complementarity problem (LCP). Under a suitable condition, the solution of LCP is equivalent to find the solution of an absolute value equations AVE. For its numerical solution, we propose an efficient two-steps fixed point iterative method for solving the AVE. Moreover, we show that this method converges globally linear to the unique solution of the AVE and which is in turn an optimal solution of SCQO. Some numerical results are reported to demonstrate the efficiency of the proposed algorithm. Mathematics Subject Classification (2010): 90C20, 90C33, 14K30. Received 18 February 2022; Accepted 27 April 2022